2020
DOI: 10.1097/wnf.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate-Responsive Tremor in a Novel Pathogenic Variant of SPG15 Patient

Abstract: Hereditary spastic paraplegia (HSP) is group of a rare neurodegenerative disorder with both genetically and clinically diverse neurologic features. Indeed, disease progression is varying greatly within the different forms and current treatment modalities are exclusively symptomatic for HSP. Tremor in HSP patients is only mentioned with rare case reports, so treatment option is lack in clinical ground. We reported a case of a HSP-15 girl with a previously reported novel mutation of SPG15 complained of a life di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Alecu et al 42 described an 18-year-old patient with CAPN1 missense mutation (SPG76) who presented with psychiatric symptoms followed by spastic gait, intention tremor, and neurogenic bladder dysfunction. Ersen et al 43 reported a case of a SPG15 patient with topiramate-responsive tremor. There are rarely described cases of orthostatic tremor associated with SPG, one of them with improvement after the use of levodopa.…”
Section: Movement Disorders In Spgmentioning
confidence: 99%
See 1 more Smart Citation
“…Alecu et al 42 described an 18-year-old patient with CAPN1 missense mutation (SPG76) who presented with psychiatric symptoms followed by spastic gait, intention tremor, and neurogenic bladder dysfunction. Ersen et al 43 reported a case of a SPG15 patient with topiramate-responsive tremor. There are rarely described cases of orthostatic tremor associated with SPG, one of them with improvement after the use of levodopa.…”
Section: Movement Disorders In Spgmentioning
confidence: 99%
“… 44 45 In summary, there are reports that patients with SPG may present with tremors, including postural, task-specific resting, or kinetic tremors. 43 46 47 48 Descriptions regarding the treatment of these patients with SPG and tremors are scarce.…”
Section: Movement Disorders In Spgmentioning
confidence: 99%
“…SPG15 is a rare cause of cHSP that clinically can present with varied phenotypes with different combinations of cerebellar ataxia, pyramidal signs, macular dystrophy (Kjellin syndrome), cognitive impairment, tremor, levodopa responsive juvenile parkinsonism, oculomotor abnormalities, peripheral neuropathy and distal amyotrophy. [3][4][5][6] Learning difficulty, intellectual disability and progressive cognitive impairment are frequent in SPG15. 6 Here we report two brothers with genetically confirmed SPG15, one of them presenting with predominant spasticity and lower limb weakness, while the other with predominant ataxia with some spasticity.…”
mentioning
confidence: 99%